O espectro da teoria-prática e a produção de significados na docência em matemática - Boff, Daiane Scopel (Universidade do Vale do Rio dos Sinos, 2019)
This doctoral thesis intends to investigate how theory and practice are valued and executed on Mathematics teacher training courses. Analyticaly supported on theorizations of Michel Foucault, on the later thought of Ludwig Wittgenstein and its commentators, and on studies about contemporary teaching, the usage of theory and practice is described concerning Mathematics teaching and it is analyzed how, from all of these, are produced utterances that operate on Mathematics teaching and signals ways of being a teacher on contemporaneity. The research material, which is composed by Mathematics teacher narratives who teach in Mathematics graduation Southern of the country, was produced by means of semi-structured interviews and online questionnaire. By taking teaching as matrix of experience, it was possible to perceive that the meanings of theory and practice and the genuine effects usually ascribed to such dimensions compose what I named the theory-practice spectrum, which, in its various gradations, allow to (re)produce ways do understand and evaluate what is done specially on teaching, what is taught and how it is taught. In the analysis undertaken, it is defended the thesis that Mathematics teaching, in such courses, gears dichotomized theory-practice spectra that typify and hierarchize mathematical and pedagogical knowledge. The non-immediate relation with some reality is a sufficient condition for the knowledge to be considered pure abstraction/formalism, therefore, taken only as theoretical. Concerning the key of reading proposed by the theory-practice spectrum, it can be concluded that, regarding to teaching in Mathematics, by valuing mathematical and pedagogical knowledge in the theoretical dimension or in the practical dimension only, ways of teaching that prioritize either what is in the order of the concrete and everyday-like or what is in the order of abstraction and formalism are constructed, which re-inscribes contemporary teaching and the very formation of teachers of Mathematics in the dichotomous pedagogical tradition that stems from the doctrine of the two worlds.
Keywords: Docência em Matemática; Docência como matriz de experiência; Dicotomia teoria-prática; Espectro da teoria-prática; Educação Matemática; Mathematics teaching; Teaching as matrix of experience; Theory-practice dichotomy; Theory-practice spectrum; Mathematical education; ACCNPQ::Ciências Humanas::Educação